Rizofiltración de plomo del agua de la piscina de relaves de la minera orenas s.a. Del Cantón Camilo Ponce Enríquez-Azuay, utilizando coriandrum sativum (culantro) en humedales artificiales (2014) - Alonso Hidalgo, Verónica Alexandra (2015)
This research aims to determine the degree of purification of lead (Pb) of pool water cyanidation tailings Orenas SA company with the use of coriander in artificial wetlands, the method used for the purification of lead It will be the rhizofiltration and research is analytical experimental using spectrophotometry.